Diagnosis of Leiomyosarcoma after Uterine Artery Embolization for Multiple Leiomyomas. (3rd November 2020) - Tsuji, Maako; Kihara, Tomoko; Hushimi, Shuko; Nishino, Yukari; Kanayama, Tomoko; Nishijima, Mitsuhiro
Abstract : Uterine sarcoma is significantly rarer than leiomyoma and has poor prognosis. Moreover, the diagnosis of leiomyosarcoma is difficult because its symptoms, including pelvic pain, uterine mass, and/or uterine bleeding, are very similar to those of leiomyoma. There are a few cases of leiomyosarcoma wherein leiomyoma was treated with uterine artery embolization (UAE); these reports revealed that the symptoms of hypermenorrhea or/and pelvic pain persisted even after UAE. Symptoms persisting even after UAE treatment for leiomyomas, especially multiple leiomyomas, should be investigated to rule out leiomyosarcoma. Therefore, long-term follow-up is needed. Here, we describe a case of a 39-year-old woman diagnosed with leiomyosarcoma 3 years after undergoing UAE for multiple leiomyomas.